MEDIA PEMBELAJARAN AUDIO VISUAL: LITERATURE REVIEW - Fatmawati Fatmawati; Wahyu Sukartiningsih; Titik Indarti (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2021)
The use of media and learning methods is the right solution for basic education teachers to develop students' skills. The media most likely to be applied in schools is the use of audio media. The research objective was to determine the benefits of audio-visual media in learning the speaking skills of low-grade students (Elementary School). This type of research uses qualitative research with literature review methods. The library selection technique is based on audiovisual media keywords on speaking skills. The literature comes from accredited national journals on Google Scholar with a publication limit of the last 10 years. The literature study technique uses a synthetic matrix based on reference sources, types of samples, methods, interventions, and findings. The results obtained in this study are as many as 12 journals about audio-visual learning media. The conclusion of this study is that it is found that audio-visual media that can be applied in the learning process include the audiobilingual method assisted by wayang media, the VAKS method (Visual, auditors, kinesthetic, suggestopedia), role playing learning using audio-visual media, the re-reading method - said with the aid of a tape recorder, learning model SAVI (Somatis Auditory Visual Intellectual), learning using film media, learning retelling methods using audio-visual media.